Controlled Transformations of Aryl Halides in a Flow System: Selective Synthesis of Aryl Azides and Aniline Derivatives. Issue 9 (6th April 2018) - Georgiádes, Ádám; Ötvös, Sándor B.; Fülöp, Ferenc
Abstract: Copper‐mediated nitrogenation of aryl halides with sodium azide can result in either aryl azides or aniline derivatives. The selectivity of the transformation is highly dependent on reaction time and temperature, which led to contradictory literature results with respect to product selectivity and the conditions applied. The advantages of a strictly controlled flow reactor environment were exploited in order to facilitate selective haloarene transformations. Reaction conditions were carefully investigated to understand their role on product selectivity. Aryl azides and aryl amines were successfully prepared from the same starting materials using the same auxiliaries by means of precise control over residence time and reaction temperature, thereby ensuring time‐, cost‐ and atom‐efficient syntheses. Abstract :